2010
DOI: 10.14742/ajet.1060
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the role of the e-tutor

Abstract: As online learning environments continue to evolve, both teachers and students need to adapt to make the most of opportunities afforded by these environments for teaching and learning. The focus of this paper is on the changing role undertaken by tutors in online learning environments. We present a brief review of the current perspectives on the roles and responsibilities suggested for the e-tutor for effective teaching, and then report on a study where roles of e-tutors in a large wholly online unit were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 15 publications
(14 reference statements)
0
40
0
5
Order By: Relevance
“…Einstructors or e-tutors now play a very important role in these learning environments. However, while they play a crucial role in e-learning success, they face many new challenges in higher education (Goold, Coldwell, & Craig, 2010). Rapidly evolving developments in e-learning raise the question of the roles required of online tutors, the skills and competencies that underpin these roles, and the need for training and professional development opportunities (Bennet & Marsh, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Einstructors or e-tutors now play a very important role in these learning environments. However, while they play a crucial role in e-learning success, they face many new challenges in higher education (Goold, Coldwell, & Craig, 2010). Rapidly evolving developments in e-learning raise the question of the roles required of online tutors, the skills and competencies that underpin these roles, and the need for training and professional development opportunities (Bennet & Marsh, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interacting in an online environment is very different from interacting in a face-to-face classroom (Denis, Watland, Pirotte, & Verday, 2004;Goold et al, 2010). E-tutors require a paradigm shift in their perceptions of instructional time and space, virtual management techniques, and ways of engaging students through virtual communications (O'Neil, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As early as 2002, Barker (2002) wondered whether educational institutions are providing adequate training and support for staff development in the important and rapidly growing area of online tutoring. An explorative study found that the experience of the e-tutor impacts on support of virtual online collaboration (Kopp et al 2012), and another study reported a need for guidance and training of novice e-tutors (Goold et al 2010).…”
Section: Role Of Tutormentioning
confidence: 99%
“…Ο εκπαιδευτής ενημερώνει συστηματικά τους σπουδαστές για το χρονοδιάγραμμα υποβολής των ασκήσεων, τους τροφοδοτεί με οδηγό μελέτης ανά διδακτική ενότητα που στοχεύει στην διευκόλυνση της οργάνωσης της μελέτης του εκπαιδευόμενου και τους καθοδηγεί για τη δημιουργία της τελικής εργασίας, η οποία διατίθεται κατά την ολοκλήρωση του μαθήματος και αφορά στο σύνολο της ύλης. Ο εκπαιδευτής, βέβαια, δεν διδάσκει με τη κλασική έννοια, αλλά υποστηρίζει, διευκολύνει και καθοδηγεί τη μελέτη του υλικού, απαντά σε ερωτήματα, εποπτεύει την πρόοδο των σπουδαστών και επισημαίνει τυχόν δυσκολίες που προκύπτουν (Goold, Coldwell & Craig, 2010).…”
Section: ομάδες ωφελούμενων και στόχοιunclassified